Implementasi Teknologi Tepat Guna Insinerator dalam Pengelolaan Sampah Pertanian dan Domestik di Desa Pakuan, Kecamatan Narmada, Kabupaten Lombok Barat - Joko Sumarsono; Amuddin; Endang Purnama Dewi; Gagassage Nanaluih De Side (Universitas Mataram, 2026)
Pakuan Village, Narmada Sub-district, West Lombok Regency, is an agrarian area with continuously growing tourism potential; however, it still faces serious challenges in managing agricultural and domestic waste. The common practices of uncontrolled disposal and open burning pose risks of environmental pollution, health problems, and a decline in the attractiveness of the village as a tourism destination. This community service activity aimed to enhance local community capacity in waste management through operational training on the use of an incinerator as an appropriate technology. The activities comprised an initial survey, educational sessions on waste characteristics and potential, hands-on training in incinerator operation, as well as mentoring and evaluation. The target participants were members of the Pakuan Village waste management team. The results demonstrated a significant improvement in participants’ understanding and skills in identifying waste types, applying standard operating procedures, and operating the incinerator safely and in an environmentally friendly manner. Evaluation results indicated that 90% of participants were categorized as having good to very good understanding of the operation and maintenance of the equipment. The implementation of the incinerator effectively reduced waste volume, minimized pollution risks, and supported environmental cleanliness in the village. Overall, this activity contributed to strengthening environmental awareness, empowering the community, and supporting the development of Pakuan Village as a sustainable agrarian and tourism village.